AKTIVITAS ANTIJAMUR KRIM EKSTRAK ETANOL DAUN SIRIH MERAH (Piper betle L. var Rubrum) PADA KELINCI BETINA YANG DIINFEKSI Candida albicansATCC® 10231 - Dwi Ningsih; Aneng Ardiya Sukmawanti; Gunawan Pamudji Widodo (Fakultas Farmasi Universitas Setia Budi, 2015)
Piper betle L. var Rubrumbe one of herbal that have historically been used as an antifungal. Flavonoid, alkaloid, saponin, tannin, and essential oils that consisting in it was expectedhave antifungal activity. Thestudy aimto determine theantifungal activity ofPiper betle l. var Rubrumleaves ethanol extract creamon female rabbit infectedCandida albicans ATCC® 10231. The antifungal experiment of Piper betle L. var Rubrumdone by infecting vagina New Zealand White rabbits with Candida albicans ATCC® 10231. Forty-eight hours after infection, vaginal smeared with 96% ethanol extract of Piper betel leaf concentration of 2.5%, 5%, 10%, and ketoconazole 2% as a positive control. Clinical symptoms that arise in the rabbit vagina during healing were observed and the number of fungal colonies of rabbit vagina calculated. The data obtained were analyzed with Anova methods with significant level of 95%, followed by SNK test. The results showed that 96% ethanol extract cream Piper betel leaf concentration of 2.5%, 5%, and 10% have antifungal effect. Cream with a 10% concentration was the most effective as an antifungal.